The Utilization of turmeric and curcuma xanthorrhiza as feed additive for broilers - Sinurat, A.P.; Purwadaria, T.; Bintang, I.A.K.; Ketaren, P.P.; Bermawie, N.; Raharjo, M.; Rizal, M. (Indonesian Animal Sciences Society, 2009)
The use of plant bioactives to replace antibiotics are now widely investigated. Turmeric or Curcuma longa (CL) and curcuma xanthorrhiza (CX), are commonly used by human and known to have active ingredients as antimicrobial. Therefore a research was conducted to evaluate the possibility of using these plant bioactives to replace antibiotic in poultry feed. The bioactives concentration of the CL and CX powder were measured prior to the feeding trial and then supplemented into standard diets of broiler chikens. The levels tested in this trial were based on the active ingredients that could inhibit growth of bacteria and fungi, i.e., low, medium and high levels of the CL and CX, respectively. The combination of low level of CL + high level of CX and low level CL +Â medium level of CX were also tested. A diet without feed additives and with antibiotics were used as controls. Each diet was fed from day old to 35 days old, replicated 6 times and each replication consist of 15 birds. Results showed that neither the antibiotic tested nor the turmeric (CL), xanthorrhiza (CX) nor the mixture of CL and CX gave significant (P>0.05) improvement on performances (body weight, FCR and mortatlity), nutrient digestibility of feed and carcass yield of broilers. Key Words: Â Broilers, Curcuma Longa, Curcuma Canthorrizhol, Bioactive